Association between prolonged stress caused by COVID-19 pandemic and earthquakes and quality of life, anxiety, depression, psychoactive substances, and problematic alcohol use in adult Croatian population - Kovačić Petrović, Zrnka; Peraica, Tina; Blažev, Mirta; Kozarić-Kovačić, Dragica (Frontiers in Psychiatry, 2024)
Background: The prolonged stress experience caused by COVID-19 pandemic and two earthquakes led to increased alcohol and psychoactive substances use (PSU), accompanied by a decrease in mental well-being and quality of life (QoL) in Croatian population. Our aim was to determine the relationship between alcohol and PSU and mental health outcomes including anxiety and depression, and QoL. Methods: A cross-sectional online survey conducted from September 30th to October 17th, 2021 included 1118 Croatian adults (220 men and 898 women; mean age: 35.1±12.3 years), recruited through non-probabilistic convenience sampling. The survey consisted of a self-reported questionnaire on PSU, the CAGE Alcohol Questionnaire, the Hospital Anxiety Depression Scale, and the World Health Organization Quality of Life (WHOQoL) – BREF. Structural equation modelling was used to evaluate the association between PSU, problematic alcohol use (PAU), mental health outcomes, and QoL. Results: The model demonstrated good fit and indicated that PSU increase, PAU, and anxiety and depression symptoms significantly explained all QoL domains (p<0.001 for all). Both PSU increase and PAU during the prolonged stress were directly associated with decreased QoL. These relationships were also indirectly mediated through increased anxiety and depression symptoms. Conclusion: These results showed the need to direct public health interventions and treatment interventions during and after long-term stress (pandemics and earthquakes) reduce the negative impact on the substance use and QoL by reducing depression and anxiety which ultimately may contribute to the better well-being and rapid recovery of individuals affected by prolonged stress.